PENGEMBANGAN MEDIA PEMBELAJARAN PLYWOOD DOOR JENIUS KEI PADA MATA PELAJARAN IPS SISWA KELAS V SD NEGERI 04 PALEMBANG - Asvera Sefta Hanifa; Bukman Lian; Kiki Aryaningrum (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2023)
The research background is that students have difficulty understanding the material, the learning activities carried out by the teacher do not use learning media. The aim of this research is to develop Plywood Door Jenius Kei learning media in social studies subjects, especially class V elementary school. The model in this research is the development of ADDIE, where there are 5 stages, namely Analyze (Analysis) analyzing the background, concepts and learning resources, Design (Design/Planning) by designing learning media products, Development (Development) namely the stage of developing learning media products through validation of material experts, language experts and media experts, Implementation, namely the application of learning media to students where a model for filling out question questionnaires is also applied. The research results from the material expert validation test results were 89%, the language expert validation test results were 90%, and the media expert validation test results were 89%. Based on the results of the validation test, it is suitable/valid for use. Based on the research results above, it can be concluded that this product can be used in the learning process of fifth grade elementary school students.   Keywords: ADDIE model, jenius kei plywood door, learning media